The fractal structure of limit set of solution space of a doubly periodic Ricatti equation - Ke-Ying Guan (International Journal of Mathematics and Mathematical Sciences)
The limit set of the Kleinian group of a given doubly periodic Riccati equation is proved to have a fractal structure if the parameter δ(λ) of the equation is greater than 3+22, and a possible Hausdorff dimension is suggested to the limit set.